Finite Element Analysis of Excavator Driving Axle Housing under the Multi Work Condition - Zhao Ya; Wang Lifang (Jixie chuandong)
In order to improve the reliability of model design,a certain type of excavator driving axle housing is regarded as the research object,the reliability interference principle is used to establish a reliable model of drive axle housing,the axle housing model size parameters are regarded as random variables,the stress and strain change rule and parameters sensitivity variation of axle housing model are studied.